CALLUS INITIATION AND SOMATIC EMBRYOGENESIS FROM CULTURED LEAF EXPLANTS OF Gladiolus hybrid (Mesopotamia Journal of Agriculture)
The present study was carried out in Plant Tissue Culture laboratory, from August . ( 2008 ) to February ( 2009 ), of Gladiolus plants " White prosperity " cv. Medium and base parts of leaves produced in vitro cultured on MS medium supplemented with NAA at ( 0.0 , 1.0 , 2.0 , 4.0 , 6.0 ) mg/l , 2,4-D at ( 0.0 , 0.01 , 0.02 , 0.1 , 0.2) mg/l , TDZ at ( 0.0 , 1.0 , 2.0 , 3.0 , 4.0 ) mg/l for callus initiation and differentiation , The Results indicated that highest percentage 90 % for callus formation were obtained from culture parts of leaf on MS medium supplemented with 0.2 mg/l 2,4-D . and this treatment gave highest amount of callus and needed only (30) days to callus formation , callus culture on MS medium supplemented with BA at ( 0.0 , 0.1 , 0.2) mg/l for differentiation , gave 80 % of callus differentiation to shoots and gave 10 shoot / explant with longest shoot 6.5 cm and highest root number 17 root / explant with longest root 4.3 cm after 8 weeks . Somatic embryogenesis obtained from culture callus produced from culture base of leaf on MS medium supplemented with 0.2 mg/l 2,4-D for 8 weeks and then culture on MS medium free from hormones , three stage of Somatic embryogenesis observed ( globular, heart , terbenoid ) embryos were development from culture on MS medium supplemented with 0.2 mg/l IAA and acclimated in laboratory with survival 100 % , plants produced from tissue culture or from feiled had the same number of chromosome (60) and this indicate that there are no somaclonal variations between them .